2018
DOI: 10.1088/1748-9326/aab2b5
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the potential for reservoirs to secure future surface water yields in the world’s largest river basins

Abstract: Surface water reservoirs provide us with reliable water supply, hydropower generation, flood control and recreation services. Yet reservoirs also cause flow fragmentation in rivers and lead to flooding of upstream areas, thereby displacing existing land-use activities and ecosystems. Anticipated population growth and development coupled with climate change in many regions of the globe suggests a critical need to assess the potential for future reservoir capacity to help balance rising water demands with long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Given our methodological approach, the variation in water yield between the two models stemmed solely from surface depressions (e.g., floodplain and non‐floodplain wetlands, ponds, and other water storage systems). This is a new finding commonly overlooked in basin‐scale/global water availability assessments (e.g., Liu et al, 2018; Veldkamp et al, 2017; Zhou et al, 2016). While Lehner et al (2011) similarly suggested the considerable potential influence of small surface water storage systems on downstream waters, our study is, to our knowledge, the first to quantify this phenomenon in one of the world's major river basins.…”
Section: Resultsmentioning
confidence: 79%
“…Given our methodological approach, the variation in water yield between the two models stemmed solely from surface depressions (e.g., floodplain and non‐floodplain wetlands, ponds, and other water storage systems). This is a new finding commonly overlooked in basin‐scale/global water availability assessments (e.g., Liu et al, 2018; Veldkamp et al, 2017; Zhou et al, 2016). While Lehner et al (2011) similarly suggested the considerable potential influence of small surface water storage systems on downstream waters, our study is, to our knowledge, the first to quantify this phenomenon in one of the world's major river basins.…”
Section: Resultsmentioning
confidence: 79%
“…After that, most five sensitive parameters have been performed for inter-connectivity between dominant characteristic using Kendall, Pearson, and Spearman methods (Table 4 ). Kendall, Pearson, and Spearman are rank correlation coefficient methods that indicate an original association between two variables (Dhar et al 2014 ; Liu et al 2018 ). It is a non-parametric hypothesis test for a relationship between two variables.…”
Section: Resultsmentioning
confidence: 99%
“…The second and third inequality constraints are the capacity limitations both in terms of system size (Z) and rate of commodity transfer ( Z). Storage losses (i.e., evaporation and seepage) are given by the factor λ and computed as a function of the estimated evaporation from the hydrological model and a linear area-volume relationship (Liu et al, 2018c). The sub-annual time period duration t converts the storage change calculated as a rate into a volume consistent with the storage level.…”
Section: Enhancements To the Messageix Modelmentioning
confidence: 99%